2006
DOI: 10.1086/510529
|View full text |Cite
|
Sign up to set email alerts
|

The Arches Cluster Mass Function

Abstract: We have analyzed H and K_s-band images of the Arches cluster obtained using the NIRC2 instrument on Keck with the laser guide star adaptive optics (LGS AO) system. With the help of the LGS AO system, we were able to obtain the deepest ever photometry for this cluster and its neighborhood, and derive the background-subtracted present-day mass function (PDMF) down to 1.3 Msun for the 5 arcsec-9 arcsec annulus of the cluster. We find that the previously reported turnover at 6 Msun is simply due to a local bump in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(169 citation statements)
references
References 18 publications
11
156
2
Order By: Relevance
“…>200 d & >40 d for 30 Dor and R136 proper; Schnurr et al 2008aSchnurr et al , 2009b) and the additional X-ray selected candidates. This is consistent with other surveys which find similarly high percentages for OB and Wolf-Rayet stars, albeit for different samples of stars comprising either lower (Clark et al 2008;Ritchie et al 2009) or a wider range of masses (Kobulnicky & Fryer 2007;Sana et al 2008;Bosch et al 2009). Such a binary fraction potentially presents important constraints on the formation mechanisms for very massive stars such as CXO J1745-28 and the Arches population.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 92%
See 1 more Smart Citation
“…>200 d & >40 d for 30 Dor and R136 proper; Schnurr et al 2008aSchnurr et al , 2009b) and the additional X-ray selected candidates. This is consistent with other surveys which find similarly high percentages for OB and Wolf-Rayet stars, albeit for different samples of stars comprising either lower (Clark et al 2008;Ritchie et al 2009) or a wider range of masses (Kobulnicky & Fryer 2007;Sana et al 2008;Bosch et al 2009). Such a binary fraction potentially presents important constraints on the formation mechanisms for very massive stars such as CXO J1745-28 and the Arches population.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 92%
“…Spitzer IRAC photometry is not available, although the theoretical model suggests (Reid 1993). These correspond to absolute F205W magnitudes of -6.4 to -7.2 mag for a uniform K-band extinction of A K s = 3.1 mag (Kim et al 2006) and (identical) distance of 8 kpc. As such, one would expect that CXO J1745-28 to be amongst the most luminous of the WN9h stars in the Galactic Centre region.…”
Section: Irtf/spex Spectroscopymentioning
confidence: 93%
“…While they basically confirmed the strong flattening of the slope in the central regions, they also found evidence of a sharp turnover in the mass function around 6−7 M that they interpreted as a low-mass truncation in the cluster IMF. A new investigation of Arches by Kim et al (2006b) using the AO camera of the Keck telescope confirmed a flatter slope and revealed the ∼6 M feature as a local maximum in the cluster mass function. With appropiate parameters as input, this bump was also reproduced later by the coalescence-collapse model of Dib et al (2007).…”
Section: Introductionmentioning
confidence: 92%
“…Although previous investigations have noted these large star-to-star extinction variations towards the Arches, they have chosen to apply an average extinction correction (Kim et al 2006b), or to subtract a radial term for radii >0.2 pc, assuming the reddening in the cluster core to be uniform (SGB02; SBG05). Our data show that the radial trend results from the area of high extinction located SW of the cluster center.…”
Section: Magnitude Limit Effectmentioning
confidence: 99%
“…Observations of the Arches cluster initially showed a shallow IMF (Figer et al 1999;Stolte et al 2002) and a turnover mass, hence a typical mass, at a few solar masses (6−7 M , Stolte et al 2005). However, Kim et al (2006) do detect low-mass stars with their deep photometry and merely find a local bump at ∼6.3 M and a somewhat shallower IMF (Γ = −1.0 to −1.1). Dib et al (2007) confirm these results and claim a top-heavy IMF.…”
Section: Introductionmentioning
confidence: 99%